The Influence of Self-control of Glycemia and Blood Pressure in the Development of Complications of Diabetes in Time Social Isolation at Covid 19 Pandemic - Jashi, Liana; Peshkova, Tamar; Dundua, Ketevan; Kvanchakhadze, Rusudan; Margalitadze, Eter (European Scientific Journal, ESJ, 2023)
Managing chronic diseases in conditions of social isolation is quite difficult and requires the development of adequate services. There is no diabetes registry in our country, therefore it is not possible to determine the needs of patients. The aim of the study is to compare the opinion of diabetic patients and doctors regarding the management of the disease during the covid-19 pandemic in the conditions of social isolation. How adequately were simple tools such as self-monitoring of blood glucose and blood pressure in the apartment used during isolation. Material and methods: a cross-sectional study method using a special questionnaire was selected for the research design. Two questionnaires were developed for doctors and diabetic patients. During the isolation 11% of patients did not monitor blood glucose level, According to doctors opinion, 3% of patients did not test for blood glucose, In the group of patients, 19.5% did not test their blood pressure. Conclusion: according to the data of the mentioned study, it is clear that inadequate control of glycemia and blood pressure in diabetic patients increases the risk of developing cardiovascular disease and death.